Analisis ekspor kopi Indonesia - Rexsi Nopriyandi; Haryadi Haryadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This study aims to analyze the factors that influence Indonesian coffee exports. The data in this study is time series data, which were obtained from various government agencies. The Error Correction Model (ECM) method is used to analyze the effect of coffee prices, GDP and the exchange rate on the volume of Indonesian coffee exports. The estimation results find that coffee prices, Indonesian GDP and exchange rates have a short-term relationship and a long-term balance of the volume of coffee exports. Based on the long-term estimation of the coffee price variable, GDP and exchange rates do not significantly affect the volume of coffee exports, while in the short term these three variables influence the volume of coffee exports